Investigating the relationship of serum levels of afamin and interleukin-10 with insulin resistance in infertile women with polycystic ovary syndrome - Gürbüz, Tuğba; Gökmen, Oya; Demirçivi Bör, Ergül; Uluocak, Aygül (Journal of Surgery and Medicine, 2021)
Background/Aim: The prevalence of Polycystic Ovary Syndrome (PCOS) is between 6-10% globally, and more than 50% of patients with PCOS are obese. The development of insulin resistance (IR) and hyperinsulinemia due to overweight can contribute to this syndrome's clinical complications. This study aimed to investigate the relationship between serum levels of afamin and Interleukin-10 (IL-10) with IR in infertile women with PCOS. Methods: Eighty-eight participants between the ages of 18 and 36 years, with at least one year of unsuccessful attempts to have children were included in this prospective case-control study. The PCOS and healthy controls were divided into two groups based on IR. Follicle Stimulating Hormone (FSH), Luteinizing Hormone (LH), Estradiol (E2), Prolactin, Thyroid Stimulating Hormone (TSH), Free T4, Anti-Mullerian Hormone (AMH), Hemogram, total cholesterol, LDL, HDL, Triglyceride, fasting blood glucose, fasting insulin, Homeostatic Model Assessment for Insulin Resistance (HOMA-IR), afamin, IL-10 values were measured. Results: The body mass indexes (BMIs) of the groups were significantly different (P<0.001); and the highest BMI was observed in the PCOS group with IR (HOMA-IR ≥2.5). Fasting insulin was significantly higher in the two groups with IR: 15.3 (6.09) in PCOS patients and 12.7 (2.8) in patients without PCOS (P=0.02). There was a weak positive correlation between BMI and Afamin (P=0.005), a strong negative correlation between BMI and IL-10 (P<0.001), a moderate negative correlation between Waist Hip Ratio (WHR) and IL-10 (P<0.001), a weak negative correlation between fasting insulin and IL-10 (P=0.001), and a weak positive correlation between monocyte and IL-10 (P=0.03). Conclusion: Our results showed an increase in Afamin and a decrease of interleukin-10 in infertile women with polycystic ovary syndrome and insulin resistance.